Animist Phytofilm: Plants in Amazonian Indigenous Filmmaking - Patrícia Isabel Lontro Vieira (Philosophies, 2022)
Early films about plants offer a glimpse into the behavior of vegetal life, which had hitherto remained hidden from humans. Critics have praised this animistic capacity of cinema, allowing audiences to see the movement of beings that appeared to be inert and lifeless. With these reflections as a starting point, this article examines the notion of animist cinema. I argue that early movies still remained beholden to the goal of showing the multiple ways in which plants resemble humans, a tendency we often still find today in work on critical plant studies. I discuss the concept of animism in the context of Amazonian Indigenous societies as a springboard into an analysis of movies by Indigenous filmmakers from the region that highlight the plantness of human beings. I end the essay with an analysis of Ika Muru Huni Kuin’s film Shuku Shukuwe as an example of animist phytocinema.